Influence of sand on the mechanical properties of metakaolin geopolymers - Kuenzel, C.; Li, L.; Vandeperre, Luc; Boccaccini, Aldo R.; Cheeseman, C. R. (Construction and Building Materials, 2014)
Metakaolin geopolymers require a high water content to have appropriate rheology for use in some applications and these mixes exhibit extensive drying shrinkage and cracking. This work aimed to understand the effect of adding sand as inert filler to metakaolin geopolymers. It is found that the viscosity increases with sand addition and mortars become unworkable when more than 40 vol% sand is added. Linear drying shrinkage was reduced from about 8% in the absence of sand to less than 1% with 38 vol% sand addition. Moreover, geopolymer mortars containing more than 15 vol% sand can withstand drying at 110 °C without cracking. Because sand addition to metakaolin geopolymer mortars increases viscosity less than a reduction in water content it is possible to formulate mortars that flow but do not crack on drying and these materials have potential for use in a range of architectural and restoration applications. © 2014 Elsevier Inc. All rights reserved.
Keywords: Drying shrinkage; Fillers; Geopolymers; Mechanical properties; Mortars